Potential prospects of supercritical CO2 power cycles for commercialisation: Applicability, research status, and advancement. (February 2023) - Ehsan, M. Monjurul; Awais, Muhammad; Lee, Sangkyoung; Salehin, Sayedus; Guan, Zhiqiang; Gurgenci, Hal
Abstract: The excellent thermo-physical and chemical properties of CO2 suggest its employment as a working fluid in power sectors owing to several benefits over the steam cycle. The present review emphasizes the potential prospects of supercritical CO2 power cycles in terms of its current status and advancement of its components. This is continuing investigation towards the attainment of safe operation at such high working pressures and temperatures. Numerous studies on supercritical CO2 (sCO2 ) power cycles in various layouts (standalone and combined) are reported with the major findings applicable for different energy sectors. The current state art of the experimental facilities with CO2 power cycle working under trans -critical/supercritical states in various research institutes is elucidated. For initial commercialization, these facilities provide a pathway for operational demonstration and control strategies. The enhancement in thermo-hydraulic performance and effectiveness of recuperators demands the execution of innovative and advanced techniques in conventional recuperators. Printed circuit heat exchangers are considered to be the most pertinent recuperators which possess the inimitable properties of augmented efficiency, impressive against withstanding higher temperature/pressure and especially their ample performance during operating conditions despite the drastic variations in thermophysical properties of supercritical fluid. The improvement in thermo-hydraulic performance of conventional recuperators after incorporating the novel geometric configurations has been extensively reviewed in this study. Moreover, the impact of non-linear variation of thermodynamic properties of supercritical fluid on efficiency, performance and stability of turbomachineries (centrifugal compressor and gas turbines) has also been broadly demonstrated through the recent experimental and numerical investigations. This research article certainly will contribute towards the development of future power generation by clean energy technologies to subside the alarming energy crisis. This article will also contribute to the development of renewable and sustainable energy sectors. Highlights: Potential prospects of supercritical CO2 power cycles for Commercialization. Cycle layouts, thermodynamic modelling, and system performance are analyzed. Research studies and development with recuperator and turbomachinery are presented. Various experimental facilities with supercritical CO2 power cycles are reported. Technical challenges, current CO2 projects, and future directions are presented.